Anthranilamide-based Short Peptides Self-Assembled Hydrogels as Antibacterial Agents - Aldilla, Vina R.; Chen, Renxun; Martin, Adam D.; Marjo, Christopher E.; Rich, Anne M.; Black, David StC; Thordarson, Pall; Kumar, Naresh (Scientific reports, 2020)
In this study, we describe the synthesis and molecular properties of anthranilamide-based short peptides which were synthesised via ring opening of isatoic anhydride in excellent yields. These short peptides were incorporated as low molecular weight gelators (LMWG), bola amphiphile, and C 3 -symmetric molecules to form hydrogels in low concentrations (0.07–0.30% (w/v)). The critical gel concentration (CGC), viscoelastic properties, secondary structure, and fibre morphology of these short peptides were influenced by the aromaticity of the capping group or by the presence of electronegative substituent (namely fluoro) and hydrophobic substituent (such as methyl) in the short peptides. In addition, the hydrogels showed antibacterial activity against S . aureus 38 and moderate toxicity against HEK cells in vitro .